A New Nanocomposite Based on Pt‐rGO Embedded Polymelamine Formaldehyde Nanocomposite for Reduction of Carbon Dioxide. Issue 6 (19th March 2021) - Alinajafi, Hossein A.; Ensafi, Ali A.; Rezaei, B.
Abstract: Here, polymelamine formaldehyde was decorated on the surface of reduced graphene oxide whose surface was then electrodeposited with a sub‐monolayer of platinum nanoparticles. The nanocomposite thus prepared was characterized using several spectroscopic methods. Using the nanocomposite as a potential electrocatalyst for carbon dioxide reduction, the products were detected by Raman spectroscopy, gas chromatography, 13 C‐NMR spectroscopy, and gas chromatography‐mass spectrometry. The analytical results identified methanol as the main product of CO2 reduction. Moreover, analysis of the liquid products confirmed methanol as the predominant product with a current density of 0.4 mA/cm and a Faradaic efficiency of 93 %. Abstract :